2016
DOI: 10.1038/srep28058
|View full text |Cite
|
Sign up to set email alerts
|

IL-22 dampens the T cell response in experimental malaria

Abstract: A tight regulation between the pro– and anti–inflammatory immune responses during plasmodial infection is of crucial importance, since a disruption leads to severe malaria pathology. IL-22 is a member of the IL-10 cytokine family, which is known to be highly important in immune regulation. We could detect high plasma levels of IL-22 in Plasmodium falciparum malaria as well as in Plasmodium berghei ANKA (PbA)-infected C57BL/6J mice. The deficiency of IL-22 in mice during PbA infection led to an earlier occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 60 publications
(86 reference statements)
1
17
0
Order By: Relevance
“…Splenocytes were isolated as described previously ( 35 ). Blood was collected using heparinized syringes and washed in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Splenocytes were isolated as described previously ( 35 ). Blood was collected using heparinized syringes and washed in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmodium berghei ANKA infected red blood cells were stored in liquid nitrogen in a solution containing 0.9% NaCl, 4.6% sorbitol and 35% glycerol. Infection was performed as previously described 45 . Briefly, C57BL/6 mice were infected with Plasmodium berghei ANKA-infected red blood cells intraperitoneally (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Two independent studies have demonstrated that in the absence of IL-22 (IL-22 KO mice) pathology cause by Plasmodium spp. infection is more severe (88, 92). Again, whether this IL-22 is coming from ILC3 is not known.…”
Section: Ilc and Plasmodiummentioning
confidence: 99%